The Impact of Local Welfare Offices on Children's Enrollment in Medicaid and SCHIP - R. Andrew Allison (SAGE Publishing, 2003)
Nearly 20% of children entering Kansas' State Children's Health Insurance Program (SCHIP) and more than 25% of children entering the state's Medicaid program leave public health insurance altogether before completing a full year of coverage, when the first redetermination of eligibility should occur. Analyses of administrative data indicate that high rates of premature disenrollment are strongly associated with case management practices at local social services offices. However, local offices enroll the vast majority of children into public health insurance. To avoid a potential trade-off between local offices' impact on enrollment and retention, the study suggests that states such as Kansas consider improvements in automation to support caseworkers' difficult jobs.